2017
DOI: 10.1111/sdi.12634
|View full text |Cite
|
Sign up to set email alerts
|

Dialysate sodium and intradialytic hypotension

Abstract: Intradialytic hypotension (IDH) is a common complication in hemodialysis, particularly with the time and frequency constraints of standard session delivery in contemporary practice. High intradialytic weight gain (IDWG), high ultrafiltration rates (UFR), and frequent IDH are highly interlinked, and separately or together contribute to the high cardiovascular morbidity and mortality observed in the hemodialysis population. Using a lower concentration of sodium in the dialysate (D-Na) reduces sodium delivery to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Nonetheless, in an exploratory analysis we found patients who reported a longer DRT category in the incident period had higher unadjusted 6-, 12-and 24-month hospitalization rates, which is similar to prior ndings in prevalent HD [15]. Other limitations of our study include not accounting for dialysate sodium, which has been found to be inversely associated to DRT presumably on account of higher hemodynamic instability [15,22,23]. However, the gradient in blood/dialysate sodium and potential variations in intradialytic tonicity might be independently associated to longer DRT.…”
Section: Discussionsupporting
confidence: 78%
“…Nonetheless, in an exploratory analysis we found patients who reported a longer DRT category in the incident period had higher unadjusted 6-, 12-and 24-month hospitalization rates, which is similar to prior ndings in prevalent HD [15]. Other limitations of our study include not accounting for dialysate sodium, which has been found to be inversely associated to DRT presumably on account of higher hemodynamic instability [15,22,23]. However, the gradient in blood/dialysate sodium and potential variations in intradialytic tonicity might be independently associated to longer DRT.…”
Section: Discussionsupporting
confidence: 78%
“…Limitations of our study include not accounting for dialysate sodium, which has been found to be inversely associated to DRT presumably on account of higher hemodynamic instability (15,22,23). However, the gradient in blood/dialysate sodium and potential variations in intradialytic tonicity might be independently associated to longer DRT.…”
Section: Discussionmentioning
confidence: 90%
“…It is unclear if modification of sodium, whether in the dialysate or in the diet, is beneficial in HFrEF. Higher dialysate sodium can reduce the incidence of intradialytic hypotension but also leads to higher interdialytic weight gains, which necessitates a higher UFR, increasing the risk of intradialytic hypotension and associated morbidities 34 . The most recent guidelines for the management of HFrEF state that dietary sodium restriction is reasonable, as it may reduce fluid retention and congestive symptoms but may be associated with higher hospitalization rates thought to be mediated through increased neurohormonal activation 9,35,36 .…”
Section: Dialysis Modality and Dialysis‐related Treatment Strategies mentioning
confidence: 99%